PENGGUNAAN MODEL NHT BERBANTUAN POP-UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 1 KAMBERA - Apu, Salestina Tamu; Ina, Anita Tamu; Matulessy, Yoin Meissy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to describe the improvement of students’ learning outcomes after the implementation of the cooperative learning model Numbered Heads Together (NHT) assisted by Pop-up Book media integrated with crossword puzzles in the topic of the human reproductive system for Grade IX students of SMP Negeri 1 Kambera. The problem identified was that only 38.46% of students achieved mastery, due to monotonous learning processes, teacher-centered lectures, and limited media variation. To address this issue, the study applied the NHT cooperative learning model combined with Pop-up Book media and interactive student worksheets (LKPD). The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through cognitive tests (post-tests), affective observations using assessment rubrics, and documentation, then analyzed quantitatively. The results showed a significant improvement in both cognitive and affective domains. In the pre-cycle stage, mastery was only 19% (cognitive) and 23% (affective). After implementing the NHT model with the support of Pop-up Book media and interactive worksheets, mastery increased to 62% (cognitive) and 69% (affective) in cycle I, and further reached 92% (cognitive) and 96% (affective) in cycle II. Overall, there was a 73% increase across both aspects. Thus, it can be concluded that the implementation of the NHT cooperative learning model assisted by Pop-up Book media and interactive worksheets is effective in improving students’ learning outcomes, both cognitively and affectively, in Grade IX E of SMP Negeri 1 Kambera. ABSTRAKPenelitian ini, bertujuan untuk mendeskripsikan bagaimanakah peningkatan hasil belajar peserta didik setelah penerapan model kooperatif tipe Numbered Head Together berbantuan media Pop-up Book dilengkapi TTS pada materi sistem reproduksi manusia di kelas IX SMP Negeri 1 Kambera. Berdasarkan permasalahan ditemukan bahwa hanya 38,46% hasil belajar siswa yang tuntas, karena proses pembelajaran yang monoton, berpusat pada ceramah guru, serta kurang variasi media. Untuk mengatasi masalah ini, penelitian menerapkan model pembelajaran kooperatif tipe Numbered Head Together (NHT) yang dipadukan dengan media Pop-up Book dan Lembar Kerja Peserta Didik (LKPD) interaktif. Penelitian dilaksanakan dalam dua siklus, yang masing-masing mencakup tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Data diperoleh dari tes kognitif (post-test), pengamatan afektif melalui rubrik pengamatan, serta dokumentasi, kemudian dianalisis secara kuantitatif. Hasil penelitian memperlihatkan adanya peningkatan signifikan pada ranah kognitif dan afektif siswa. Pada tahap pra siklus, ketuntasan kognitif hanya 19% dan afektif 23%. Setelah menggunakan model NHT dengan dukungan Pop-up Book dan LKPD interaktif, ketuntasan meningkat menjadi 62% (kognitif) dan 69% (afektif) pada siklus I, lalu mencapai 92% (kognitif) dan 96% (afektif) pada siklus II. Secara keseluruhan, terjadi kenaikan sebesar 73% pada kedua aspek. Dengan demikian, dapat disimpulkan bahwa penerapan model kooperatif NHT berbantuan Pop-up Book dan LKPD interaktif efektif dalam meningkatkan hasil belajar siswa, baik kognitif maupun afektif, pada kelas IX E SMP Negeri 1 Kambera.